2017
DOI: 10.1097/hjh.0000000000001429
|View full text |Cite
|
Sign up to set email alerts
|

Improved treatment and control of hypertension in Swedish primary care

Abstract: BP control in hypertensive patients attending Swedish primary care has improved over 5-7 years, and more so in high-risk groups. There is, however, room for improvement. In uncontrolled hypertension the combination of several drug classes remain low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A likely explanation for the decline in non-OAC ICH incidence is improved detection and control of hypertension [11, 35]. Two Swedish studies have shown an increased number of patients with antihypertensive treatment but importantly also improved BP control between 1986 and 2009 and 2001/2002–2007/2008, respectively [36, 37]. Still, about half of the patients did not achieve adequate BP control indicating that even more cases of ICH can be prevented using established treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A likely explanation for the decline in non-OAC ICH incidence is improved detection and control of hypertension [11, 35]. Two Swedish studies have shown an increased number of patients with antihypertensive treatment but importantly also improved BP control between 1986 and 2009 and 2001/2002–2007/2008, respectively [36, 37]. Still, about half of the patients did not achieve adequate BP control indicating that even more cases of ICH can be prevented using established treatment.…”
Section: Discussionmentioning
confidence: 99%
“…High blood pressure is a leading modifiable cause of premature death [ 1 ]. In Sweden, approximately, a third of the grown-up population is affected [ 2 , 3 ]. Many patients with hypertension do not reach recommended blood pressure targets and are thereby exposed to an unnecessary – but treatable – elevated risk of disease and death [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment is often based on severity of the hypertension, and patients preferences are not always considered [ 16 ]. One reason for lack of goal achievement, whether it is reaching the target BP or achieving successful lifestyle modifications, is presumably the limited opportunities for a shared understanding of health needs and everyday commitment to treatment [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%